Factors Affecting Volume Changes of the Somatosensory Cortex in Patients with Spinal Cord Injury: To Be Considered for Future Neuroprosthetic Design - Höller, Yvonne; Tadzic, Arijan; Thomschewski, Aljoscha C.; Höller, Peter; Leis, Stefan; Tomasi, Santino Ottavio; Hofer, Christoph; Bathke, Arne; Nardone, Raffaele; Trinka, Eugen (Frontiers in Neurology, 2017)
Spinal cord injury (SCI) leads to severe chronic disability, but also to secondary adaptive changes upstream to the injury in the brain which are most likely induced due to the lack of afferent information. These neuroplastic changes are a potential target for innovative therapies such as neuroprostheses, e.g. by stimulation in order to evoke sensation or in order to suppress phantom limb pain. Diverging results on grey matter atrophy have been reported in patients with SCI. Detectability of atrophy seems to depend on the selection of the regions of interest, while whole-brain approaches are not sensitive enough. In this study, we discussed previous research approaches and analysed differential atrophic changes in incomplete SCI using manual segmentation of the somatosensory cortex. Patients with incomplete SCI (ASIA C-D), cervical (N=5) and thoracic (N=6) injury were included. Time since injury was <=12 months in 7 patients, and 144, 152, 216, and 312 months in the other patients. Age at the injury was <=26 years in 4 patients, and >=50 years in 7 patients. A sample of 12 healthy controls was included in the study. In contrast to all previous studies that used voxel-based morphometry, we performed manual segmentation of the somatosensory cortex in the postcentral gyrus from structural magnetic resonance images and normalized the calculated volumes against the sum of volumes of an automated whole-head segmentation. Volumes were smaller in patients than in controls (p=.011), and female patients tended to have smaller volumes than male patients (p=.017, uncorrected). No effects of duration (subacute vs. chronic), level of lesion (cervical vs. thoracic), region (left vs. right S1), and age at onset (<=26 years vs. >=50 years) was found. Our results demonstrate volume loss of S1 in incomplete SCI and encourage further research with larger sample sizes on volumetric changes in the acute and chronic stage of SCI, in order to document the moderating effect of type and location of injury on neuroplastic changes. A better understanding of neuroplastic changes in the sensorimotor cortex after SCI and its interaction with sex is needed in order to develop efficient rehabilitative interventions and neuroprosthetic technologies.